Internal Medicine Residency Program in Guyana: A Collaborative Model for Sustainable Graduate Medical Education in Resource-Limited Settings - Persaud, Dev; Cole, Joanna; Jainarine, Ramdeo; Khalid, Zahira (Frontiers in Public Health, 2017)
The Georgetown Public Hospital Corporation (GPHC) started the Internal Medicine/Infectious Diseases residency program in 2013. It was a collaborative initiative between GPHC and University of Maryland. Since that time the program has gone through many trials and developed new partnerships and collaboration and emerged as a young successful program with close international links that have worked and persevered in developing the successful academic and professional careers of its residents. International collaborations have resulted in applying innovative methods of teaching to deliver the curriculum in a sustainable manner in a resource-limited setting. The article discusses in detail the history of the program and the roles that the collaborative partners have played in the evolution of the program.